Facebook use and its predictive factors among students: Evidence from a lower- and middle-income country, Bangladesh - Al-Mamun, Firoj; Hosen, Ismail; Griffiths, Mark D.; Mamun, Mohammed A. (Frontiers in Psychiatry, 2022)
Background: Facebook is a popular social-networking site in the modern world. It has an adverse effect such as impairing daily activities, psychological health and also interpersonal relationship when the use become problematic. Aims: To examine problematic Facebook use (PFU) and its predictors in Bangladesh during the COVID-19 pandemic. Method: A cross-sectional online survey was conducted among 601 Bangladeshi students and collected data related to socio-demographic information, behavioral health, internet use behavior, depression, anxiety and Problematic Facebook use (assessed using the Bergen Facebook Addiction Scale [BFAS]). The data were analyzed using descriptive (frequencies and percentages) and inferential statistics (independent sample t-tests, one-way ANOVAs, correlations, and multivariable linear regression). Results: The results indicated that 29.1% of participants were problematic Facebook users (using cutoff ≥18 out of 30). Medical college students had higher mean score on PFU than other students (p<0.001). In addition, the mean score of PFU was significantly higher among the students who were in a relationship (p=0.001), did not engage in physical activity (p<0.001), used the internet more than five hours per day (p<0.001), used social media (p<0.001), and had depression or anxiety symptoms (p<0.001). PFU was significantly associated with depression and anxiety among the whole sample. Predictive factors for PFU included relationship status, daily internet use time, gaming, social media use, depression, and anxiety. The model predicted almost 33.2% variance for PFU. Conclusions: Findings suggest interventions should be implemented for students with a special focus on medical students who had higher score of PFU than other types of students